Influence of environmental conditions on performance and heart rate responses to the 30-15 incremental fitness test in rugby union athletes - Natera, A. O. W.; Jennings, J.; Oakley, A. J.; Jones, T. W. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to examine the differences in performance and heart rate (HR) responses between a high heat outdoor condition (34.0° C, 64.1% humidity) and a temperate indoor condition (22.0° C, 50.0% humidity) during the 30-15 intermittent fitness test (30-15IFT). Eight highly trained Rugby Union players (28.1 ± 1.5 years, 181.4 ± 8.8 cm, 88.4 ± 13.3 kg) completed the 30-15IFT in 2 different temperature conditions. Dependent variables recorded and analyzed included: final running speed of the 30-15IFT, HR at rest (HR rest), maximum HR (Max HR), HR recovery, average HR (HR ave), and submaximal HR corresponding to 25, 50, and 75% of final test speed (HR 25%, HR 50%, and HR 75%) and HR at 13 km/h (HR 13 km/h). Greater running speeds were achieved when the test was conducted indoors (19.4 ± 0.7 km/h vs. 18.6 ± 0.6 km/h, p = 0.002, d = 1.67). Average HR and HR 13 km/h were greater when the test was conducted outdoors (p = 0.05, d > 0.85). Large effect sizes were observed for the greater HR at submaximal intensities (d > 0.90). The results of this study highlight the influence of temperature on 30-15IFT performance and cardiac responses. It is recommended that prescription of training based on 30-15IFT results reflects the temperature that the training will be performed in and that practitioners acknowledge that a meaningful change in assessment results can be the result of seasonal temperature change rather than training-induced change.